2017
DOI: 10.1037/neu0000304
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain markers are differentially associated with neurocognitive profiles in socially marginalized people with multimorbid illness.

Abstract: Homeless and marginally housed individuals constitute a socially impoverished population characterized by high rates of multimorbid illness that includes polysubstance use, viral infection, and psychiatric illness. Their extensive exposure to risk factors is associated with numerous poor outcomes, yet little is known about structural brain integrity and its association with neurocognition in this population. In Study 1, we conducted a cluster analysis to re-construct three previously derived subgroups with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 156 publications
(301 reference statements)
2
28
1
Order By: Relevance
“…Living in marginal housing, such as single‐room occupancy (SRO) hotels is associated with serious consequences for health, well‐being, and psychosocial functioning (Vila‐Rodriguez et al, ). Co‐occurring polysubstance use, infectious diseases, and severe psychiatric illnesses are commonplace (Krausz et al, ; Vila‐Rodriguez et al, ) and entail significant costs, such as neurocognitive impairments (Gicas et al, ). These impairments may be central to the psychosocial dysfunction of marginalized persons.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Living in marginal housing, such as single‐room occupancy (SRO) hotels is associated with serious consequences for health, well‐being, and psychosocial functioning (Vila‐Rodriguez et al, ). Co‐occurring polysubstance use, infectious diseases, and severe psychiatric illnesses are commonplace (Krausz et al, ; Vila‐Rodriguez et al, ) and entail significant costs, such as neurocognitive impairments (Gicas et al, ). These impairments may be central to the psychosocial dysfunction of marginalized persons.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we characterized extensive neurocognitive impairment of marginalized persons living in SRO hotels by grouping participants across multiple neurocognitive domains (attention, memory, executive functioning). Three subgroups with unique profiles of neurocognitive impairments were differentiated by cortical gyrification and thickness (Gicas et al, ). Our prior findings suggested that the poorest performing subgroup showed evidence of greater neurodevelopmental brain aberrations, whereas greater environmental risk exposures characterized persons in the other two subgroups.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations